Comparison of nicotine exposure during pregnancy when smoking and abstinent with nicotine replacement therapy: systematic review and meta‐analysis. (11th December 2018) - Hickson, Charlotte; Lewis, Sarah; Campbell, Katarzyna Anna; Cooper, Sue; Berlin, Ivan; Claire, Ravinder; Oncken, Cheryl; Coleman‐Haynes, Tom; Coleman, Tim
Abstract: Background and aims: Smoking during pregnancy is strongly associated with negative pregnancy and perinatal outcomes. Some guidelines recommend nicotine replacement therapy (NRT) for smoking cessation during pregnancy, but adherence with NRT is generally poor and could be partially explained by nicotine‐related safety concerns. We compared pregnant women's cotinine and nicotine exposures from smoking with those when they were abstinent from smoking and using NRT. Design: Systematic review with meta‐analysis and narrative reporting. Twelve studies were included: in most, only one type of NRT was used. Seven were quality‐assessed and judge of variable quality. Setting: Studies from any setting that reported nicotine or cotinine levels when smoking and later when abstinent and using NRT. Participants: Pregnant women who smoked and became abstinent but used NRT either in a cessation study or in a study investigating other impacts of NRT. Measurements: We quality‐assessed longitudinal cohort studies using a modified version of the Newcastle–Ottawa scale. For meta‐analysis, we used mean within‐person differences in cotinine or nicotine levels when smoking and at later follow‐up when abstinent and using NRT. Where such data were not available, we calculated differences in group mean levels and reported these narratively, indicating where data were not completely longitudinal. Findings: Of the 12 included studies, four cotinine‐measuring studies ( n = 83) were combined in a random effects meta‐analysis; the pooled estimate for the mean difference (95% confidence intervals) in cotinine levels between when women were smoking and abstinent but using NRT was 75.3 (57.1 to 93.4) ng/ml ( I 2 = 42.1%, P = 0.11). Of eight narratively‐described studies, six reported lower cotinine and/or nicotine levels when abstinent and using NRT; two had mixed findings, with higher levels when abstinent but using NRT reported from at least one assay time‐point. Conclusions: Pregnant women who use nicotine replacement therapy instead of smoking reduce their nicotine exposure.